Study of Anti-Herpetic Activity of a Soft Dosage form With Acyclovir and Miramistin - Kienko LS (Journal of Global Pharma Technology, 2020)
The aim of the present work is to study the anti-herpetic action of the soft dosage form with acyclovir and miramistin on the model of herpes simplex virus. Using in vitro methods were studied cytotoxic concentration of substances, effective concentration, index of selectivity of substances and disinfectant action. Non-germinal guinea pigs were divided into three groups. Group I was infected with herpes virus, group II was infected with herpes virus and treated with the soft dosage form with acyclovir (5 g / 100 g) and miramistin (0.5 g / 100 g) and group III was infected with herpes virus and treated with 5 % Zovirax cream. It has been proven that the soft dosage form with acyclovir and miramistin is an active inhibitor of the reproduction of herpes virus type 2. Keywords: Acyclovir, Miramistin, Herpes viral diseases, Soft dosage form.